Mechanical properties of low-carbon ultrahigh-performance concrete with ceramic tile waste powder. (14th June 2021) - Xu, Kaicheng; Huang, Wenyi; Zhang, Liqing; Fu, Shucheng; Chen, Mengcheng; Ding, Siqi; Han, Baoguo
Highlight: With CTWP replacing 55% cement, low-carbon UHPC with acceptable mechanical properties for structural use is developed. Adding 25%–35% CTWP can obviously improve mechanical properties of UHPC. Low-carbon UHPC with CTWP shows obvious superiority in environmental impact and material cost. Abstract: In this paper, ceramic tile waste powder (CTWP) was used to replace cement in to prepare whole-life low-carbon ultrahigh-performance concrete (UHPC). The mechanical properties, modification mechanism, environmental impact and cost of UHPC with 15–55% CTWP were investigated. The results indicated that the compressive and flexural strength of the UHPC with CTWP are all higher than 120 MPa and 14 MPa at 28 d within the error range, respectively. The mechanical properties of UHPC with 35% CTWP maximally improved at 28 d, while the mechanical properties of UHPC with 55% CTWP all decreased by less than 10% at 28 d. The modification mechanism of CTWP on UHPC mainly included the pozzolanic effect, nucleation effect and filling effect, which were proven by pozzolanic activity analysis, TG-DTA, SEM and MIP. CTWP possesses pozzolanic activity and can improve the hydration degree of cement by as much as 51.4%. Furthermore, the addition of 35% CTWP decreased the ITZ, total porosity, and number of mesopores of UHPC by 15.70%, 4.38%, and 42.04%, respectively. Moreover, environmental impacts and cost analysis were also performed, and the energy intensity, CO2 emissions, and material cost of UHPC are reduced by 41.0%, 33.1%, and 25.9%, respectively, with the addition of 55% CTWP. UHPC with 55% CTWP is a promising whole-life low-carbon concrete.